Humeral anatomy of the KNM-ER 47000 upper limb skeleton from Ileret, Kenya: Implications for taxonomic identification. Issue 126 (January 2019) - Lague, Michael R.; Chirchir, Habiba; Green, David J.; Mbua, Emma; Harris, John W.K.; Braun, David R.; Griffin, Nicole L.; Richmond, Brian G.
Abstract: KNM-ER 47000 is a fossil hominin upper limb skeleton from the Koobi Fora Formation, Kenya (FwJj14E, Area 1A) that includes portions of the scapula, humerus, ulna, and hand. Dated to ∼1.52 Ma, the skeleton could potentially belong to one of multiple hominin species that have been documented in the Turkana Basin during this time, including Homo habilis, Homo erectus, and Paranthropus boisei . Although the skeleton lacks associated craniodental material, the partial humerus (described here) preserves anatomical regions (i.e., distal diaphysis, elbow joint) that are informative for taxonomic identification among early Pleistocene hominins. In this study, we analyze distal diaphyseal morphology and the shape of the elbow region to determine whether KNM-ER 47000 can be confidently attributed to a particular species. The morphology of the KNM-ER 47000 humerus (designated KNM-ER 47000B) is compared to that of other early Pleistocene hominin fossil humeri via the application of multivariate ordination techniques to both two-dimensional landmark data (diaphysis) and scale-free linear shape data (elbow). Distance metrics reflecting shape dissimilarity between KNM-ER 47000B and other fossils (and species average shapes) are assessed in the context of intraspecific variation within modern hominid species ( Homo sapiens, Pan troglodytes, Gorilla gorilla, Pongo pygmaeus ). Our comparative analyses strongly support attribution of KNM-ER 47000 to P. boisei . Compared to four other partial skeletons that have (justifiably or not) been attributed to P. boisei, KNM-ER 47000 provides the most complete picture of upper limb anatomy in a single individual. The taxonomic identification of KNM-ER 47000 makes the skeleton an important resource for testing future hypotheses related to P. boisei upper limb function and the taxonomy of isolated early Pleistocene hominin remains.